Mycorrhizal colonization of indigenous tropical tree species grown in peat swamp forests of Sumatera, Indonesia. (August 2019) - Turjaman, M; Herdyantara, B; Faulina, S A; Agustini, L; Irianto, R S B; Hidayat, A; Wahno, I; Murdani,; Tjahyono, B; Indrayadi, H
Abstract: The restoration of peat swamp forests in Sumatra island has become Indonesian government's priority to restore ecological functions and their utilization. Indigenous. However, little information is available on the status of arbuscular mycorrhizal (AM) fungi in Sumatera. The objective of this research was to know AM fungi colonization in indigenous of tropical peat swamp forests. Root samples of 28 tree species in 14 families grown in a peat swamp forest of Jambi, Riau, and South Sumatera. All soil and tree roots were grown in zeolite media and trapped in Pueraria javanica and Shorgum bicolor as host plants for four months in a green house. Roots were stained with 0.1% trypan blue and vesicles, arbuscles and internal hyphae of AM fungi observed under a compound microscope. The results have shown that 20 tree species (72%) were colonized by AM fungi, 4 tree species of the dipterocarps family (14%) were colonized by ectomycorrhizal fungi (ECM), and four other tree species (14%) did not find FMA or ECM colonization. It is suggested that utilization of mycorrhizas can increase early growth of some tree species grown in peat swamp forests and mycorrhizal application will be expected as a key technology to restore degraded peatlands.